2016
DOI: 10.1007/s00374-016-1127-3
|View full text |Cite
|
Sign up to set email alerts
|

Invasive plants affect arbuscular mycorrhizal fungi abundance and species richness as well as the performance of native plants grown in invaded soils

Abstract: We studied the effects of invasions by three plant species: Reynoutria japonica, Rudbeckia laciniata, and Solidago gigantea, on arbuscular mycorrhizal fungi (AMF) communities in habitats located within and outside river valleys. Arbuscular mycorrhizal colonization, AMF abundance and species richness in soils were assessed in adjacent plots with invaders and native vegetation. We also quantified the performance (expressed as shoot mass, chlorophyll fluorescence, and the concentration of elements in shoots) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 41 publications
3
67
2
4
Order By: Relevance
“…Several studies (e.g., Richardson et al 2000;Hawkes et al 2006;Rodríguez-Echeverría et al 2009;Oehl et al 2010;Carneiro et al 2015;Souza et al 2016b) also showed a lower AMF diversity in disturbed soils by biological invasion of invasive exotic species (e.g., A. senegal, A. seyal, A. albida, E. albensis, Olpidium spp., Cryptostegia madagascariensis, Sesbania virgata, P. juliflora, and Parkinsonia aculeata) in comparison with soil in natural conditions. These results are in agreement with previous studies (Soumare et al 2015;Ayanu et al 2015;Zubek et al 2016;Callaway et al 2008;Tanner and Gange 2013) and support our hypothesis that invasive plants are associated with specific AMF species. As a consequence, P. juliflora seemed to be in advantage comparing with M. tenuiflora by profiting from beneficial AMF species (e.g., AMF from the order Glomerales) (Shah et al 2009).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Several studies (e.g., Richardson et al 2000;Hawkes et al 2006;Rodríguez-Echeverría et al 2009;Oehl et al 2010;Carneiro et al 2015;Souza et al 2016b) also showed a lower AMF diversity in disturbed soils by biological invasion of invasive exotic species (e.g., A. senegal, A. seyal, A. albida, E. albensis, Olpidium spp., Cryptostegia madagascariensis, Sesbania virgata, P. juliflora, and Parkinsonia aculeata) in comparison with soil in natural conditions. These results are in agreement with previous studies (Soumare et al 2015;Ayanu et al 2015;Zubek et al 2016;Callaway et al 2008;Tanner and Gange 2013) and support our hypothesis that invasive plants are associated with specific AMF species. As a consequence, P. juliflora seemed to be in advantage comparing with M. tenuiflora by profiting from beneficial AMF species (e.g., AMF from the order Glomerales) (Shah et al 2009).…”
Section: Discussionsupporting
confidence: 94%
“…These results are in agreement with previous work (Soumare et al 2015;Majewska et al 2015) that reported higher values of soil pH and available P in the root zone of invasive exotic plants, such as Acacia senegal, Acacia seyal, Acacia albida, Eragrostis albensis, and Olpidium spp. By altering the chemical properties of the soil below their canopy, invasive plant species may alter the nutrient cycle (Follstad Shah et al 2010) and thus may be responsible for the modification AMF community composition in the EXO soils (Zubek et al 2016;Zubek et al 2013). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…plants change the abundance, diversity, and structure of plant and animal communities (Hejda et al 2009;Lenda et al 2013), and often considerably modify physicochemical and biological properties of the soil environment, thereby potentially affecting key ecosystem processes (Vilà et al 2011;Castro-Díez et al 2014;Majewska et al 2015;Stefanowicz et al 2016;Zubek et al 2016;Broadbent et al 2017;CastroDíez and Alonso 2017;Lavoie 2017;Rodríguez-Caballero et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The invasion of another nonmycorrhizal plant, Reynoutria japonica Houtt. decreased the species richness and AM fungal abundance due to reduction of organic carbon inputs (Zubek et al, 2016). AM fungi enhance the extensive spread and invasiveness of Solidago canadensis more than the native Stipa bungeana Trinius plant species (Sun & He, 2010).…”
Section: Role Of Mycorrhizal Symbiosis In Plant Invasionmentioning
confidence: 99%